Improvement of Audit and Accounting of Fixed Assets (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article is devoted to the analysis of modern approaches to improving the audit and accounting of fixed assets. It examines common errors and challenges that arise in the accounting and auditing process, and assesses the impact of changes in legislation and standards on these processes. Particular attention is paid to the study of modern audit tools and methods, including automation, the use of artificial intelligence and big data, the use of blockchain technologies and Remote auditing capabilities. The article emphasizes the importance of International Standards on Auditing to ensure the uniformity and transparency of financial reporting at the international level. The conclusion of the article focuses on the need for an integrated approach to improving accounting and auditing processes, which includes both strict adherence to regulatory requirements and active implementation of the latest technologies and methods in audit practice.